Reading the romance - Radway, Janice A. (The University of North Carolina Press, 1991)
Challenges popular (and often demeaning) myths about why romantic fiction, one of publishing's most lucrative categories, captivates millions of women readers. In a new introduction, author Radway places the book within the context of current scholarship and offers both an explanation and critique of the study's limitations.–From publisher description.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Appréciation; Femme; Femmes - Livres et lecture; Femmes dans la littérature; Féminisme et littérature; Féminisme; Histoires d'amour - Appréciation; Lecture; Littérature populaire; Paralittérature - Appréciation; Patriarcat (Sociologie); Roman d'amour; Rôle selon le sexe dans la littérature; Rôle selon le sexe; Thème littéraire; Frau; Feminism and literature; Love stories; Patriarchy; Popular literature; Sex role in literature; Women in literature; Women; Trivialer Frauenroman; Frauenroman; Trivialroman; Trivialliteratur; Englisch; Leserin